THE PROBLEM OF TEACHING ENGLISH IN ELEMENTARY SCHOOL-BASED ON TEACHER INVOLVED: EXPLORING TEACHER'S PERSPECTIVE - Noor, Zulfikar; Harahap, Addinul Kamil; Dewi, Utami (LLT Journal: A Journal on Language and Language Teaching, 2023)
English-teaching problem is an important issue that has been discussing and in diverse contexts around the world, including English teacher problems, students, assessments, curricula and textbooks, and the various variables that contribute to effective English as a foreign language (EFL) teaching, for this reason, the purpose of the study is to explore 10 participants’ perspective in issues of teaching English in ELT classroom. This descriptive qualitative study investigated how teachers perceived the English teaching issue based on the teachers involved. Data were collected using a questionnaire that includes a single primary question about the use of Teaching-English issues that were raised by teachers. This study came to three main conclusions: (1) Teachers' emotional control. (2) Personal experience of teachers. (3) The teacher's interest in the character of the pupil. (4) Teaching staff accountability. Finally, Problems with teaching English should not be understated because they have a significant impact on how well students learn the language in elementary schools. To continuously improve their teaching skills without becoming complacent, teachers must be aware of their shortcomings.